Phytochemical Screening of Ethanol Extract Qust Al Hindi roots (Saussurea lappa) - Rahayu, Na'am Nur Azizah; Sukmawati, Sukmawati; Rahman, Safriani (Pharmaceutical Reports, 2024)
Qust al hindi is a plant from the Asteraceae family which has various therapeutic effects in ancient medicinal systems. This plant is used in traditional medicine in Arab countries as a stimulant, carminative, sedative and astringent. The part of Qust al hindi plant that is most often used for medicinal purposes is the dried root of the plant. This study aims to determine the content of secondary metabolites contained in the root extract of the plant Qust al Hindi. The extraction process was carried out by the soxhletation method using 96% ethanol at 70ºC, and followed by phytochemical screening. The results of the phytochemical screening of the ethanol extract of the Qust al Hindi roots positively contained alkaloids, flavonoids and terpenoids.